Structure de la marge continentale norvégienne au débouché de la mer de Barentz - Briseid, E.; Mascle, Jean (Springer, 1975)
Reconstructions of the continents prior to the opening of the Norwegian sea indicate an overlap between the Greenland and the Norwegian continental margins just west of the Barentz sea and imply that the basement of this area is of oceanic origin. Seismic profiling shows an oceanic-type basement covered by thick Tertiary sediments. The sedimentary supply is related to the geological history of the Barentz sea where only little unconsolidated sediments are known. Further south the structures of the present margin are directly related to the early opening of the Norwegian sea. [NOT CONTROLLED OCR] La reconstitution géométrique des continents avant l'ouverture de la mer de Norvège suggère que le socle au débouché de la mer de Barentz est d'origine océanique. Un important delta sédimentaire est installé à ce niveau. Les profils de sismique réflexion montrent que les sédiments reposent sur un socle acoustique de type océanique. L'importance de la sédimentation tertiaire est expliquée par l'histoire géologique de la mer de Barentz où l'on ne connaît que de très faibles épaisseurs de sédiments non consolidés. Plus au sud, la marge continentale est d'un type différent, probablement liée à l'importance des phénomènes de cisaillement caractérisant la première phase d'ouverture de la mer de Norvège. [OCR NON CONTRÔLE]